Aspectos microbiológicos e citológicos do leite na mastite caprina subclínica - Langoni, Hélio [UNESP]; Citadella, Juliana Cristina Cardoso [UNESP]; Machado, Gustavo Puglia [UNESP]; Faccioli, Patrícia Yoshida [UNESP]; Lucheis, Simone Baldini; Silva, Aristeu Vieira da (My University, 2012)
Goat's milk is an important product in human alimentation, since it presents an elevated nutritional content indicated for children, the elderly and the disabled. It is accepted by persons who are intolerant to bovine milk. 720 samples of goat's milk were collected from 378 dairy goat´s of Saanen and Anglo-Nubian race coming from ten rural properties within the Brazilian state of São Paulo (n=8) and Minas Gerais (n=2), by California Mastitis Test (CMT), cultivating samples from the reaction +. Were isolated Staphylococcus aureus (34.6%), Staphylococcus epidermidis (26%), Staphylococcus caprae (25%), Streptococcus dysgalactiae (6.7%), Corynebacterium bovis (2.9%), Streptococcus uberis (1.9%), Escherichia coli (1.9%), and Micrococcus ssp (1%). The average of Somatic Cells Counts (SCC) range from 119.8 to 899.5 SCC/mL of milk. Despite not having found a significant correlation between CMT and SCC/mL of milk, the significant SCC increase of milk samples with reaction +++ to CMT must be considered. Consider that there is occurrence of subclinical mastitis in goats is high, the microbiota is wide and S. aureus was the most frequent.

La leche de cabra es un producto importante para la alimentación humana, y debido a su alto contenido nutricional es adecuado para niños, ancianos, personas físicamente debilitadas e individuos intolerantes a la leche de bovino. Por medio del California Mastitis Test (CMT), fueron analizadas 720 muestras de leche de 378 cabras lactantes de las razas Saanen y AngloNubiana provenientes de diez propiedades rurales del estado de São Paulo (n=8) y Minas Gerais (n=2). El cultivo de las muestras fue realizado a partir de la reacción + a CMT. Fueron aislados Staphylococcus aureus (34,6%), Staphylococcus epidermidis (26%), Staphylococcus caprae (25%), Streptococcus dysgalactiae (6,7%), Corynebacterium bovis (2,9%), Streptococcus uberis (1,9%), Escherichia coli (1,9%) y Micrococcus spp (1%). El promedio del conteo de células somáticas (CCS) varió de 119,8 a 899,5 CCS/mL de leche en las propiedades estudiadas. A pesar de no haber sido encontrada una correlación significativa entre la CMT y el CCS/mL, se debe considerar el aumento significativo de CCS en las muestras de leche con reacción +++ al CMT. La ocurrencia de mastitis subclínica en la especie caprina es alta, la microbiota es amplia y S. aureus fue el microorganismo más frecuente.

O leite caprino é um produto importante na alimentação humana, pois além de elevado teor nutritivo é indicado para crianças, idosos e pessoas debilitadas, e aceito por indivíduos que têm intolerância ao leite bovino. Foram examinadas 720 amostras de leite de 378 cabras leiteiras das raças Saanen e Anglo-Nubiana procedentes de dez propriedades rurais localizadas no estado de São Paulo e Minas Gerais, pelo California Mastitis Test (CMT), cultivando as amostras a partir da reação +. Foram isolados Staphylococcus aureus (34,6%), Staphylococcus epidermidis (26%), Staphylococcus caprae (25%), Streptococcus dysgalactiae (6,7%), Corynebacterium bovis (2,9%), Streptococcus uberis (1,9%), Escherichia coli (1,9%) e Micrococcus spp (1%). A média de Contagem de Células Somáticas (CCS) variou entre 119,8 a 899,5 CCS/mL de leite nas propriedades estudadas. Apesar de não ter-se encontrado correlação significativa entre CMT e CCS/mL de leite, devese considerar o aumento significativo da CCS nas amostras de leite com reação +++ ao CMT. Pode-se considerar que a ocorrência de mastite subclínica na espécie caprina é elevada e que a microbiota é ampla e o S. aureus foi o de maior ocorrência.
Cytological and microbiological aspects of milk on goat's subclinical mastitis
Aspectos microbiológicos y citológicos de la leche en mastitis caprina subclínica
Keywords: Goat; Milk; Microbiology; Cytology; Cabra; Leche; Microbiología; Citología; Caprino; Leite; Microbiologia; Citologia